Analysis of threats to research validity introduced by audio recording clinic visits: Selection bias, Hawthorne effect, both, or neither?. Issue 7 (July 2015) - Henry, Stephen G.; Jerant, Anthony; Iosif, Ana-Maria; Feldman, Mitchell D.; Cipri, Camille; Kravitz, Richard L.
Highlights: We investigated factors associated with consent to audio record clinic visits. We examined the effect of recording on patient–clinician interactions. Few patient or clinician factors were associated with likelihood of consent. We found no significant effects of recording on patient–clinician interactions. Abstract: Objective: To identify factors associated with participant consent to record visits; to estimate effects of recording on patient–clinician interactions. Methods: Secondary analysis of data from a randomized trial studying communication about depression; participants were asked for optional consent to audio record study visits. Multiple logistic regression was used to model likelihood of patient and clinician consent. Multivariable regression and propensity score analyses were used to estimate effects of audio recording on 6 dependent variables: discussion of depressive symptoms, preventive health, and depression diagnosis; depression treatment recommendations; visit length; visit difficulty. Results: Of 867 visits involving 135 primary care clinicians, 39% were recorded. For clinicians, only working in academic settings ( P = 0.003) and having worked longer at their current practice ( P = 0.02) were associated with increased likelihood of consent. For patients, white race ( P = 0.002) and diabetes ( P = 0.03) were associated with increased likelihood of consent. Neither multivariable regression nor propensity score analyses revealed any significant effects of recording on the variables examined. Conclusion: Few clinician or patient characteristics were significantly associated with consent. Audio recording had no significant effect on any of the 6 dependent variables examined. Practice implications: Benefits of recording clinic visits likely outweigh the risks of bias in this setting.